1992
DOI: 10.1002/crat.2170270321
|View full text |Cite
|
Sign up to set email alerts
|

On the Intensity of Kossel Reflections

Abstract: The line intensity of Kossel reflections of various single crystals ( A l , A2, B3, B4 and C16 type of structure) has been studied experimentally as well as theoretically. In contrast to earlier results high excess intensity of experimental Kossel lines can be explained solely by dynamical diffraction effects without an additional consideration of real structure effects. It has been shown that the different maxima of intensities of Kossel lines found above all result from the different line width, depending st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…These interferences are situated on cones with half-opening angles equal to 90°-Θ hkl (Θ hkl < 90°) and create the so-called Kossel lines on the X-ray detector located at the back. The line-intensity-to-background ratio is very low and amounts to only 2 % in the case of electron excitation [10,11]. Consequently, evaluating such patterns by a conventional method is difficult.…”
Section: Methodsmentioning
confidence: 99%
“…These interferences are situated on cones with half-opening angles equal to 90°-Θ hkl (Θ hkl < 90°) and create the so-called Kossel lines on the X-ray detector located at the back. The line-intensity-to-background ratio is very low and amounts to only 2 % in the case of electron excitation [10,11]. Consequently, evaluating such patterns by a conventional method is difficult.…”
Section: Methodsmentioning
confidence: 99%
“…In a forthcoming paper [21] it will be shown that remarkable differences exist in the intergrowth behaviour of a single taenite lamella with kamacite blocks.…”
Section: Discussionmentioning
confidence: 98%
“…A more complete understanding of the complex line profiles is developed by using dynamic theory of diffraction. For the discussion of the mechanisms leading to these profiles see [10,11] and references therein. The profiles of K α1 lines are additionally affected by the proximity of the K α2 lines.…”
Section: The Methodsmentioning
confidence: 99%